Analysis of Aroma Components of Enzymatic Hydrolysis Products of Oak Lignin from Different Producing Areas - Zheng, Hao (International Journal of Natural Resources and Environmental Studies, 2024)
The morphology and structure of lignin in French oak, American oak and Chinese Mongolian oak were observed and compared by scanning electron microscopy (SEM). The results showed that the surface of lignin after enzymatic hydrolysis was more irregular and the contact area was obviously increased. GC-MS detected 3 kinds of lignin, 4 kinds of components and 30 kinds of volatile substances. The lignin content of French oak was the highest (8911.5 ± 512.2 μg/L, 29 kinds), followed by that of American oak (8071.7 ±541.9 μg/L, 26 kinds), and that of Mongolian oak was the least (7903.3 ± 492.5 μg/L, 26 kinds). The results of aroma characteristics analysis, principal component analysis and heat map analysis showed that the aroma components of the three kinds of oak lignin were significantly different. French oak lignin could provide more volatile phenols, with obvious smoky, woody and sweet flavor. Mongolian oak lignin carries more phenolic and ester compounds, providing a relatively soft floral, fruity flavor. American oak lignin has a relatively average aroma substance content, which can bring strong and complex complex aroma characteristics.